Niveles de Mercurio en Orina de los profesores, alumnos y técnicos de la Clínica Odontológica de la Facultad de Odontología de la Universidad Nacional Mayor de San Marcos - Perales Zamora, Segundo (2003)
The purpose of this investigation work is to stablish the mean characteristics of the mercury range in urine so 30 professors, 11 students and 3 technicians were evaluated through a written test and an urine sample was taken from them, then they were collected 100ml sterilizing bottles. After that, they were analyzed in the chemistry services unit of the faculty of chemistry of San Marcos university through the I ASTM D ﷓3223﷓95 FLAMELES ATOMICABSOPTION SPECTRO PHOTOMETRIC METHOD. The results were: Characteristics of the study sample: the age average of the sample was 38.50 years old (standard deviation =8%). The sample had predominance of male sex (84%) and (15.9%) of female sex only. The male sex people who were interviewed said the average of clinical work was 13.19 years (standard deviation =5.37) and the female sex people said 11 years (standard deviation =1.00) the male sex group who were interviewed said the week hours average of clinical work was 15.78 (S.D =4.01) and a week hours average of particular work was 20.81 (S.D=8.52) and the female sex group said 15. 00 (S.D=5)for the second one. The results of the mercury range un urine were: in professors = 0. 033ug/ml (S.D= 0.10 ug/ml) in students= 0.00427 ug/ml (S.D 0.0866) and in technicians (who showed the highest level of all) = 0. 35 ug/ml in consideration of the maximum permissible limit is 0.002 ug/ml 27.7% of the there is a sample that overpass this limit significative. The factors related with the mercury concentration were: clinical work years (p=0. 000) week hours average of clinical work (p= 0.000) week hours average of particular work (p= 0. 000) average of amalgam restaurations performed a week (p=0.035). The signs and symptoms found in a high percentage were: gingival retraction (27.27%) halitosis (22.73%) of difficulty in remembering fresh events (25%) irritability (19.9%) hands tremor (13.63%) hand writing disturbance, (13.63%).